Global macro trading : profiting in a new world economy - Gliner, Greg (Bloomberg financial series., 2014)
"Brings global macro trading down to earth for individual and professional traders, investors and asset managers, as well being a useful reference handbookGlobal Macro Trading is an indispensable guide for traders and investors who want to trade Global Macro - it provides Trading Strategies and overviews of the four asset classes in Global Macro which include equities, currencies, fixed income and commodities. Greg Gliner, who has worked for some of the largest global macro hedge funds, shares ways in which an array of global macro participants seek to capitalize on this strategy, while also serving as a useful reference tool. Whether you are a retail investor, manage your own portfolio, or a finance professional, this book equips you with the knowledge and skills you need to capitalize in global macro. Provides a comprehensive overview of global macro trading, which consists of portfolio construction, risk management, biases and essentials to query building Equips the reader with introductions and tools for each of the four asset classes; equities, currencies, fixed income and commodities Arms you with a range of powerful global-macro trading and investing strategies, that include introductions to discretionary and systematic macro Introduces the role of central banking, importance of global macroeconomic data releases and demographics, as they relate to global macro trading "--